Strategi UMKM CV. Najwa dalam Meningkatkan Daya Saing Pemasaran Pie Susu Khas Bali - Fauzi, M. Asif Nur; Rohmah, Yusfika Fatimatur; Khoiriyah, Khoiriyah; Machrus, Ali; Nuruddin, Nuruddin (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are considered to be the driving force of the economy in Indonesia, especially in Denpasar. This can be seen from the large amount of state foreign exchange income coming from MSMEs. In the last decade, many micro businesses have emerged, whether in the form of culinary businesses, fashion, agribusiness, and others. Research with the title "Implementation of Management Systems in CV MSMEs. Najwa in the Production of Bali Gebyar Milk Pie in Denpasar", has a problem formulation on how to implement the CV management system. Najwa is good at production management, human resource management, marketing management and financial management in producing typical Balinese souvenirs, namely milk pies, seeing the island of Bali as a tourist destination so it is visited by many tourists. The type of research used is qualitative research, the data collection methods used are observation, interviews and documentation. The research results show that implementing management in a company, both large and small companies, is very necessary, because in general every company wants its business to continue running and developing in accordance with the company's goals, namely to make a profit.